1970
DOI: 10.1128/iai.2.5.563-569.1970
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of Grouped and Ungrouped Streptococci by Lysozyme

Abstract: Thirty strains of streptococci were tested for lysis with lysozyme, and 29 of these could be lysed by the following method: (i) suspension of the cells to a Klett reading of 200 units (no. 42 filter) in 0.01 M tris(hydroxymethyl)aminomethane buffer, pH 8.2, after washing twice with the buffer; (ii) addition of lysozyme to a final concentration of 250 ug/ml with incubation for 60 min at 37 C; (iii) addition of sodium lauryl sulfate (SLS) to a final concentration of 0.2% and incubation up to an additional 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…An additional control experiment was performed to determine if hen egg lysozyme injected in vivo could effect PG-APS-induced arthritis. Hen egg lysozyme is a basic protein with muramidase activity, but it is unable to degrade group A streptococcal cell wall in vitro (22)(23)(24). Rats were injected intraperitoneally with an arthropathic dose of PG-APS and randomly divided into two groups.…”
Section: Treatment Of Arthritis In Rats With Mutanolysinmentioning
confidence: 99%
“…An additional control experiment was performed to determine if hen egg lysozyme injected in vivo could effect PG-APS-induced arthritis. Hen egg lysozyme is a basic protein with muramidase activity, but it is unable to degrade group A streptococcal cell wall in vitro (22)(23)(24). Rats were injected intraperitoneally with an arthropathic dose of PG-APS and randomly divided into two groups.…”
Section: Treatment Of Arthritis In Rats With Mutanolysinmentioning
confidence: 99%
“…Based on these observations, it has been suggested that the quantity and digestibility of endocytosed material may control acid hydrolase production (29). PPG stimulated acid hydrolase production greatly, but it is not digestible by macrophages (9,11,34). Group A streptococcal cell walls can be digested partially by N-acetyl-/3-D-glucosaminidase, an enzyme found in certain soil bacteria (10).…”
Section: A Component Of Group a Streptococcal Cell Walls Induces Chromentioning
confidence: 99%
“…Its pH optimum of 3.4 is lower than that of lysozynir and its pattern of heat lability as a function of pH is opposite to that of lysozyme ( 1 1 ) . While the enzyme, like lysozyrne, liberates reducing groups and is thcrefore a glycosidase, its ability to partly degrade streptococcal cell walls prepared by glass-head breakage and enzyme digestion contrasts sharply lvith the inability of lysozyme to do so (6,8).…”
Section: Discussionmentioning
confidence: 99%
“…I n this paper ive report partial purification of this enzyme and some of its properties. I n particular, we have studied the effect of this enzyme on streptococcal cell walls, and have found that it could partially degrade certain cell-tzall preparations that resist attack hy hen egg white lysozynie (6,8 ) . Unlike lysozyme, hacteriolytic action of the enzyme includes release of the group-specific carbohydrate rendering it potentially useful for studies on streptococcal cell wall structure.…”
Section: Index Abstractmentioning
confidence: 99%